Association between vitamin D deficiency and clinical outcome in patients with COVID-19 in the post-Omicron phase - Chen, I-Wen; Yu, Ting-Sian; Lai, Yi-Chen; Yang, Chih-Ping; Yu, Chia-Hung; Hung, Kuo-Chuan (Frontiers in Nutrition, 2025)
BackgroundVitamin D deficiency (VDD) has been associated with adverse outcomes in COVID-19 patients during the early pandemic phases, but whether this association persists in the post-Omicron era remains uncertain. This study aimed to investigate the evolving relationship between VDD and COVID-19 outcomes across pandemic phases using a large healthcare database.MethodsWe conducted a retrospective cohort study using the TriNetX Analytics Network, analyzing propensity-matched cohorts comprising 24,236 pairs from the post-Omicron phase (June 2022–December 2023) and 22,638 pairs from the pre-Omicron phase (January 2020–December 2021). VDD was defined as a serum 25-hydroxyvitamin D level < 20 ng/ml, with vitamin D-sufficient patients (≥30 ng/ml) serving as controls. The primary outcome was 30-day all-cause mortality, with secondary outcomes including acute kidney injury, respiratory failure, pneumonia, sepsis, and ICU admission.ResultsThe 30-day mortality in VDD vs. vitamin D-sufficient patients decreased from 1.43% vs. 0.39% [odds ratio (OR), 3.67; 95% CI, 2.90–4.64; p < 0.001] in the pre-Omicron phase to 0.89% vs. 0.49% (OR, 1.82; 95% CI, 1.46–2.28; p < 0.001) in the post-Omicron phase. Similar risk attenuation was observed across all secondary outcomes, including acute kidney injury (OR, 2.11; 95% CI, 1.92–2.31 vs. OR, 1.41; 95% CI, 1.29–1.54; both p < 0.001), respiratory failure (OR, 1.66; 95% CI, 1.44–1.92 vs. OR, 1.34; 95% CI, 1.16–1.54; both p < 0.001), and pneumonia (OR, 1.34; 95% CI, 1.16–1.55 vs. OR, 1.23; 95% CI, 1.07–1.42; p < 0.001 and p = 0.004, respectively). Risk factor analysis identified several significant mortality predictors among patients with VDD in the post-Omicron phase, including malnutrition (OR, 4.34; 95% CI, 3.18–5.92; p < 0.001), liver disease (OR, 3.08; 95% CI, 2.23–4.25; p < 0.001), and neoplasms (OR, 2.63; 95% CI, 2.01–3.45; p < 0.001).ConclusionVDD continues to be associated with adverse COVID-19 outcomes in the post-Omicron phase, albeit with a reduced magnitude. These findings support the importance of vitamin D screening in high-risk COVID-19 patients, while emphasizing the need for adaptive risk assessment strategies that incorporate both established and emerging risk factors in the current pandemic landscape.